Evaluation of Wound Healing Activity of Aqueous Extract of Chromolaena odorata on Wistar Rats - Panda, Subham Kumar; Mishra, Sunita; Ray, B.; Sharma, V. G. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Introduction: A wound can be defined as any physical injury or break in the skin or underlying tissues caused by trauma, surgery, or various medical conditions. Wound healing is a complex and dynamic biological process that occurs in response to injury or damage to the skin or underlying tissues. Medecinal plant have been reported to show wound healing Potential via angiogenesis activation of NF-κB, favoring pro-inflammatory cytokines, increased expression of induciblenitric oxide syntheses (iNOS) and alpha 1 type 1 collagen, and anti-oxidant activity. Materials and Methods: The Present Research work Conclude the wound healing potential of standard and aqueous extract of Chromolaena odorata was studied on Wistar rat excision wound model. Results and Discussion: The topical application of standard (soframycin) showed a significantly faster wound contraction rate (70.58%) on 15th post-operative day as compared to non-treated group (33.33%). Conclusion: The topical application of standard (soframycin) showed a significantly faster wound contraction rate (70.58%) on 15th post-operative day as compared to non-treated group (33.33%). Aqueous extract of Chromolaena odorata showed wound contraction rate of (61.66%) on 15th post-operative day as compared to non-treated group (33.33%).